PRESENTACIÓN, REPRESENTACIÓN Y AFECTOS EN DOS CUENTOS ACERCA DE LA VIOLENCIA POLÍTICA EN EL PERÚ 1980-2000. - Baeza-Henríquez, Antonio (Revista Chilena de Literatura, 2023)
The article analyzes the relationship between the presentation and representation of political violence in two stories about the armed conflict in Peru between 1980 and 2000. It focuses on the stories "Adiós Ayacucho" by Julio Ortega and "Voces de Infiernillo" by Laynes, which explore the effects of violence on subalternized subjects. It discusses how reading relates to narration and affects, highlighting the differences between both stories in terms of the presentation and representation of violence. "Adiós Ayacucho" tells the story of Alfonso Cánepa, who is accused of terrorism, tortured, and murdered by agents of the Peruvian state, but continues to speak and seeks to be buried whole. The story uses humor, while "Voces de Infiernillo" amplifies the feeling of anguish and desolation. The text analyzes two stories, one of them titled "Cánepa," in which the presence of the voice is highlighted as an organic element that develops autonomously and partially in relation to the body. The use of black humor is emphasized as a resource that generates an affective complicity between the narrator and the reader. In addition, the absence of a visceral reaction to the violence represented in the narration is mentioned. On the other hand, a contrast is established between coastal and highland sensitivity, highlighting the ability of Limeños to laugh at themselves. It is suggested that this difference reflects the relationship between officialdom and Limean culture with the problem of violence in the highlands. The perpetuation of subalternity as a historical and political condition is also mentioned. In another analyzed story, titled "Voces de Infiernillo," the experience of Pascuala, a Quechua-speaking woman from Ayacucho, who suffers the violent invasion of the police and the kidnapping of her son, is narrated. The text analyzes two stories, "Adiós Ayacucho" by Julio Ortega and "Infiernillo" by Emilio Laynes, which address political violence in Peru during the war between the State and the Shining Path. Both stories present detailed descriptions of violated bodies and acts of abuse, humiliation, and indifference. The narration of the stories influences the way the reader emotionally engages with the stories, generating an atmosphere of repulsion and desolation. These texts are acts of revising the narrative code and represent the experience of those who have been forced into subalternity.